PERBEDAAN FAKTOR-FAKTOR YANG MEMPENGARUHI NILAI PERUSAHAAN ANTARA PERUSAHAAN PERBANKAN DAN NON PERBANKAN (Studi Empiris pada perusahaan keuangan perbankan dan non perbankan tahun 2010-2014 ) - Setiawati, Erma; Pardiyanto, Pardiyanto; Efendi, Ifin Aria (Riset Akuntansi dan Keuangan Indonesia, 2016)
The purpose of this study was to analyze the effect of capital structure , profitability , size , liquidity to the companys value in the banking and non-banking companies and the difference. The population in this study were the banking and non-banking companies listed on the Stock Exchange in 2010-2014 .The sampling technique was purposive sampling method . The number of samples in this study on the banking company as much as 105 companies and non-banking companies 138 companies for the period 2010-2014 .The analytical method used was multiple regression analysis and different test t-test with SPSS 22. The resuld of this study indicated that no difference variable capital structure, size, profitability and liquidity of the companys banking and non-banking finance.Â Keywords : Value of the Company, capital structure , profitability , company size , liquidity .